2002
DOI: 10.1042/0264-6021:3620247
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide and sphingosine have an antagonistic effect on the plasma-membrane Ca2+-ATPase from human erythrocytes

Abstract: The plasma-membrane Ca# + -ATPase is a key enzyme in the regulation of the intracellular Ca# + concentration. On the other hand, sphingolipids have been recognized recently as important second messengers, acting in many systems in combination with Ca# + . In view of the fact that the Ca# + -ATPase is stimulated by ethanol, and since sphingolipids possess free hydroxy groups, we decided to study the possible effect of ceramide and sphingosine on this calcium pump. Here we show that ceramide stimulates the Ca# +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…However, our experiments using two different Shaker-channel mutants, one with altered voltage dependence and one nonconducting, clearly show that neither cellular hyperpolarization nor the Shaker channel K ϩ conductance is the critical event. The activity of several membrane proteins like channels and pumps are affected by the composition of the lipid bilayer (21,22), the interaction with other membrane proteins (23,24), and by membrane protein dilution (possible via interactions with the cytoskeleton) (25). It is possible that the Shaker channel protein affects K ϩ efflux through direct or indirect interactions with apoptosis-associated channels or pumps.…”
Section: Discussionmentioning
confidence: 99%
“…However, our experiments using two different Shaker-channel mutants, one with altered voltage dependence and one nonconducting, clearly show that neither cellular hyperpolarization nor the Shaker channel K ϩ conductance is the critical event. The activity of several membrane proteins like channels and pumps are affected by the composition of the lipid bilayer (21,22), the interaction with other membrane proteins (23,24), and by membrane protein dilution (possible via interactions with the cytoskeleton) (25). It is possible that the Shaker channel protein affects K ϩ efflux through direct or indirect interactions with apoptosis-associated channels or pumps.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Cer with short fatty acid chains (C 2 -and C 8 -Cer) activates both soluble and native erythrocyte Ca 2ϩ -ATPase in a concentration range near and above the critical micellar concentration (42). In this work we explored the possibility that, in addition to a direct effect at high concentrations, probably related to physical changes in the pump molecule, Cer, in the nanomolar range expected for a second messenger, could be capable of interacting with plasma membrane signaling cascades in the close vicinity that are functionally coupled to Ca 2ϩ -ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…The skeletal muscle SR Ca 2+ -ATPase is stimulated by jasmine and jasmonate and increase the rate of dephosphorylation of the ATPase [143]. Reports show that ceramide stimulates the plasma membrane Ca 2+ -ATPase activity in a dose dependent manner and an additive effect in activation was observed in presence of calmodulin and ethanol [144]. Ceramide affects the affinity for Ca 2+ and V max of the enzyme, and also stimulates Ca 2+ transport in inside-out plasma membrane vesicles from erythrocytes.…”
Section: Regulation Ofmentioning
confidence: 99%